Distance Advanced Training of Preschool Teachers in Ukraine: Quantitative Indicators - Tetiana Sharova; Volodymyr Voronov; Sergii Sharov; Halyna Kolomoiets; Anna Voronova (Online Learning In Educational Research (OLER), 2024)
This study examines the stages involved in organizing distance learning advanced training courses and provides a quantitative analysis of preschool educators participating in the "Education and Care" program in Ukraine. The need for this study arises from the increasing reliance on distance learning formats for professional development, particularly in light of technological advancements and socio-political challenges. Despite prior research on children in preschool, there remains a lack of systematic analysis of the organizational processes and outcomes of such programs. The study utilized theoretical and empirical methods, with data collected through Google Forms and analyzed for the period of July-September 2023. Results indicate that 13,456 preschool educational professionals (principals, methodologists, and teachers) participated in the program, with preschool teachers representing the majority (71%). Only 7% of participants received completion certificates. This study highlights critical insights into the scalability and implementation of distance training programs, providing a foundation for future research and policy development in preschool education.